The politics of women’s health : (Temple University Press, 1998)
This book is an examination of both the real world of women's health status and health-care delivery in different countries, and the assumptions behind the dominant medical model of solving problems without regard to social conditions. The writing is also informed by some of the authors' own experiences with women's health issues: birth, menopause, major surgery, and providing care for mothers and grandmothers.Rather than focusing on types of medical interventions, "The Politics of Women's Health" asks what feminist health-care ethics looks like if we start with women's experiences and concerns. It begins to unravel two key concepts of women's empowerment - agency and autonomy - that apply to all areas of concern to women. Author note: Susan Sherwin is Professor of Philosophy and Women's Studies, Dalhousie University.